Viabilidade da prática de observação de aves em unidades de conservação na Amazônia: um estudo de caso na Área de Relevante Interesse Ecológico (ARIE) Japiim-Pentecoste, município de Mâncio Lima, Acre. - Plácido, Ricardo Antônio de Andrade (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
The birdwatching is one of the activities of ecotourism that grows the most in the world and at Brazil, country which shows to have great bird species diversity. Protected area‟s (PA) are privileged areas for this modality of ecotourism since they protect habitats and species of interest for the bird watchers. In this work, we developed a methodological protocol to evaluate the viability of bird observation in the protected areas of the Amazon forest. The protocol is based on evaluating the attractiveness levels of bird species recorded at the protected area‟s, the infrastructure conditions and services offered by the management, and, also, the main conditions of the municipalities near the units to host the birdwatchers. The protocol was applied in the Area of Relevant Ecological Interest (AREI) Japiim-Pentecoste located at the State of Acre. A total of 266 bird species were recorded in this a PA, of which 65 and 24 species were evaluated in having a attractiveness index, for birding, ranging from medium to high levels. There is a set of available trails that cross through the PA main areas opened by residents for their agroextractivist labours. The managing body of the protected area however, does not offer any infrastructure or facility to support visitation. The municipalities close to the PA are Mâncio Lima and Cruzeiro do Sul, and the latter offers a wide range of hotels and rental possibilities to support the bird watching activity. Few accommodation and transportation services were available in Mâncio Lima, although the municipality was located closer to the PA easing access to it. The protocol was efficient for a quick and simple analysis of the potential to the practice of bird observation in PA‟s. However, some aspects such as the diminution of subjectivity in the evaluation of the attractiveness of each species can be improved. We believe that the protocol developed in this study can be applied in other Amazon forest's PA‟s to evaluate the potential of these protected areas for the promotion of ecotourism based on birdwatching.
Keywords: Aves; Unidades de conservação; Ecoturismo